2014
DOI: 10.1590/0004-282x20140111
|View full text |Cite
|
Sign up to set email alerts
|

Psychogenic nonepileptic seizures and psychogenic movement disorders: two sides of the same coin?

Abstract: Psychogenic nonepileptic seizures (PNES) and psychogenic movement disorders (PMD) are commonly seen in Neurology practice and are categorized in the DSM-5 as functional neurological disorders/conversion disorders. This review encompasses historical and epidemiological data, clinical aspects, diagnostic criteria, treatment and prognosis of these rather challenging and often neglected patients. As a group they have puzzled generations of neurologists and psychiatrists and in some ways continue to do so, perhaps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…A strong association between functional movement disorders and exposure to phenotypically similar movement disorder models was shown [10]. Response to placebo, suggestion or psychotherapy rather than improvement with drug treatments is another finding in these patients [1,3].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…A strong association between functional movement disorders and exposure to phenotypically similar movement disorder models was shown [10]. Response to placebo, suggestion or psychotherapy rather than improvement with drug treatments is another finding in these patients [1,3].…”
Section: Discussionmentioning
confidence: 97%
“…Features that are regarded as characteristic of PMD include abrupt onset, fluctuations in symptom severity, spontaneous remissions, inconsistency, incongruency, distractibility, suggestibility, bizarre movements, deliberate slowness of movements and disproportional functional disability. Other clues are a dramatic increase of PMD by direct observation, physical or psychosocial triggers, secondary gain and normal diagnostic studies [3,6,9,12]. Somatoform disorders are also very common [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent pilot randomized controlled trial showed significant seizure reduction and improved comorbid symptoms and global functioning for psychogenic nonepileptic seizure patients that underwent cognitive behavioral treatment with or without sertraline, while treatment-as-usual or sertralineonly showed no benefit 8 . In this issue of Arquivos de Neuropsiquiatria, DePaola et al provide an extensive review of historical aspects, epidemiology, clinical features, diagnosis, and prognosis of psychogenic nonepileptic seizures and psychogenic movement disorders 9 . The authors also review the limited published data that analyzed possible common features of both disorders.…”
mentioning
confidence: 99%